Dual Marginalisation and the Demand for Dual Citizenship: Negotiating “At Homeness” Among Diaspora Liberians - Franka Vaughan (Social Inclusion)
In Liberia, identity and citizenship have long been contentious, with dual citizenship emerging as a focal point in recent decades. On 22 July 2022, former President George Weah signed an Amendment Law allowing Liberians naturalized abroad to retain citizenship and granting Liberian women the right to confer citizenship to their children, addressing a key demand from diaspora Liberians. This article, based on my doctoral thesis (Vaughan, 2022), examines diaspora Liberians’ advocacy for dual citizenship within contemporary debates on citizenship as a strategic institution. Drawing on the “post‐exclusive turn” in citizenship (Harpaz & Mateos, 2019), which suggests that individuals often prioritize a premium passport over strong ties to a homeland, the article explores how diaspora Liberians pursue dual citizenship to secure a “true home” in Liberia. This advocacy is fueled by their marginalization both in Liberia, where they face scrutiny over their Liberianness, and in their host countries, where they experience otherness as ethnic minorities. Dual citizenship, for these Liberians, is a strategic path back to belonging in Liberia. This article highlights the intricate interplay between identity and citizenship in Liberia, complicating the strategic citizenship framework by shedding light on the nuanced experiences of diaspora Liberians as they navigate dual marginalization and negotiate belonging. By focusing on these dynamics, the article contributes to the broader debate on citizenship in Africa, an area that remains understudied. Moreover, it reframes discussions on strategic citizenship, particularly in the context of growing inequalities and rising anti‐immigrant sentiments.